Effectiveness of Antenatal Exercise on Reducing Back Pain In Pregnant Women In The Second and Third Trimesters - Fani Syinthia Rahmi; Rima Wirenviona; Rahmi Melfa Widodo (Open Access Health Scientific Journal, 2026)
Background: The prevalence of back pain in pregnant women in the third trimester in 2019 globally based on a survey conducted in England and Scandinavia, there were 50% of pregnant women in the third trimester suffering from significant back pain, while in Indonesia the prevalence rate of back pain was 68% of pregnant women with moderate intensity and 32% of pregnant women experiencing back pain with mild intensity. The purpose of the study was to determine the effectiveness of antenatal exercise reducing back pain in pregnant women in the second and third trimesters at the Kampung Dalam Community Health Center, Solok Regency in 2025.Methods: This research type is a Quasy Experiment with the One-Group Pretest – Posttest Design method, conducted from August 2024 to April 2025. The population is all pregnant women in the second and third trimesters at the Kampung Dalam Sub-Health Center. In a total of 16 people with a sampling technique of total sampling. The research instrument uses an observation sheet. Univariate and bivariate analysis using the dependent t-test statistical test.Results: The results of the study showed that the average back pain before antenatal exercise in pregnant women in the second and third trimesters was 7.13, and the average back pain after antenatal exercise in pregnant women in the second and third trimesters was 4.94. The results of the dependent t-test statistical test showed that the p value = 0.000.Conclusion: The conclusion of the study is that there is effectiveness of antenatal exercise in reducing back pain in pregnant women in the second and third trimesters at the Kampung Dalam Sub-Health Center in Solok Regency in 2025. It is recommended that health workers improve the quality of health services and educate mothers and families more so that they can be more enthusiastic and routine in doing antenatal exercise in order to provide comfort in the form of reducing back pain in pregnant women.